(untitled) (Research, Society and Development, 2020)
The aim of this study was to analyze the hematological characteristics of ascitic fluids in patients at University Hospital Lauro Wanderley (HULW) as well as their importance in determining the diagnosis. The study population consisted of patients with various kind of pathologies, admitted to the HULW, of both genders, aged 18 years or over with a diagnosis of ascites. The study was carried out in accordance with the requirements of the Research Ethics Committee (CAAE 23933819.0.0000.5183) of HULW. 309 exams were analyzed, of which 68% were male and the highest incidence in the age group above 60 years (41%) with ascites predominating as the established diagnosis. Bacterial peritonitis was present in 12% of the samples and 6% had hemorrhagic aspects. These data corroborate with the literature, in which there is a predominance of males and the average age 56.4 ± 6 years, which can be attributed to the prevalence of hepatitis viruses in the population, as well as to the moment of the spread of viral infection, as well as the use of alcohol as a relevant factor to trigger cirrhosis. Among the limitations of our study, it should be noted the lack of clear information when filling out the request for the laboratory examination, as well as the adequate collection and handling of the sample, which makes the analysis of cavitary fluids difficult and prejudicial.